Book Review: Environmental Policy Convergence in Europe? The Impact of International Institutions and Trade by Katharina Holzinger, Christoph Knill and Bas Arts (Eds.). (18th June 2009) - Yang, Peter
Environmental Policy Convergence in Europe? The Impact of International Institutions and Trade, by Katharina Holzinger, Christoph Knill and Bas Arts (Eds.). Cambridge University Press, 2008. ISBN-10: 0521888816; ISBN-13: 978-0521888813